WOMEN INDEPENDENCE IN LOUISA MAY ALCOTT`S LITTLE WOMEN - Intan, Intan; Tuaderu, Yohanes (STBA Prayoga Padang, 2023)
Abstract This study aims to analyze the independence of women based on the novel Little Women by Louisa May Alcott. The novel tells a life story of four female teenagers in the March Family with Jo March – the main character – who struggles to become an independent woman. The writers are interested in the characterization of Jo who dominates her three other sisters in take the initiative to do things and in deciding the best solution whenever they face problems in the situation of the absence of their father who is still in military duty. By applying feminist existentialism theory postulated by Simone de Beauvoir, the writers analyze the forms of women independence that trigger Jo to be independent from the perspective of objectivity and transcendence. This research is qualitative research from which the data are taken from the novel and other online supporting sources. All the data are interpreted byutilizing descriptive method that views a situation or phenomenon in the novel as something important to be described based on the research problems. In the end of the research, the writers found that the triggers that encourage Jo March to become independent are the limitation of freedom in women life and social rules that demand women to get married with rich men or any men of the established class to improve a family’s social class and livingstandard as well. Besides that, this research also found that the ways that direct women to be independent is obeying mother’s advice and guidance. Mother is a woman who always dreams the best future for her children. Jo’s mother does this role very well.